The structural fire design of concrete structures with externally bonded reinforcement and fire protection system - Turkowski, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
This work describes the structural fire design process of RC structures with externally bonded reinforcement. First part is based on the calculation method given in EN 1992-1-2 and addresses the question whether the fire protection of externally bonded reinforcement is necessary in every situation? The second part shows what such fire protection should look like and how it should be designed. Moreover, a test procedure for determining the effectiveness of applied fire protection systems to concrete structural members reinforced with FRP, used in Fire Testing Laboratory of Building Research Institute (ITB) is presented.